Relationships in Patagonian species of Berberis (Berberidaceae) based on the characterization of rDNA internal transcribed spacer sequences - Bottini, Maria Cecilia Juana (2007)
Sequence analysis of the internal transcribed spacer (ITS) of the 18S(ITS1)-5.8S 26S(ITS2) rDNA region was performed in order to analyse the phylogenetic relationships between 13 Patagonian species of the genus Berberis (Berberidaceae). The divergence values between the pairwise sequence in the studied Patagonian species were in the range 2.9–22.9%. The lengths of the ITS1 and ITS2 sequences were in the range 227–231 bp and 220–224 bp, respectively, and the 5.8S sequence was 159 bp throughout all species. B. microphylla sensu Landrum does not appear to be monophyletic based on current sampling. Indeed, we suggest that B. microphylla should be distinguished from B. buxifolia, B. parodii, and B. heterophylla . ITS sequences, together with data obtained from morphological, biochemical, amplified fragment length polymorphism, and cytological characterizations, support the existence of diploid and polyploid hybrid speciation in the genus.